The Use of the Kahoot Application in PAI Learning to Improve Students' Understanding of Grade 6 at SDN 105321 Tumpatan Nibung - Lana, Maulana; Nopita Sari Harahap; Yanti Ginting; Muhammad Saleh; Bagus Taufik; Dinda Puspito Tito (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2025)
Abstract: This study aims to describe the use of Kahoot application in PAI (Islamic Religious Education) learning to improve the understanding of grade 6 students at SDN 105321 Tumpatan Nibung. The research uses qualitative methods with a descriptive approach. Data collection was carried out through observation, interviews, and documentation. The subjects of the study were PAI teachers and 6th grade students at SDN 105321 Tumpatan Nibung. The results of the study show that: (1) The implementation of the Kahoot application in PAI learning is carried out with the stages of preparation, implementation, and evaluation; (2) The use of the Kahoot application has succeeded in increasing students' understanding of PAI subjects as evidenced by an increase in students' average scores; (3) Supporting factors for the use of Kahoot include the availability of technology facilities and student enthusiasm, while inhibiting factors include limited time and technical ability of teachers. This study concludes that the Kahoot application is effectively used as an interactive learning medium to improve students understanding of PAI learning in grade 6.